Adult mesenchymal stem cells and their possibilities for Dentistry: what to expect? - José Ricardo Muniz Ferreira; Anna Paula Greck (Dental Press Editora, 2020)
ABSTRACT Introduction: Stem cells obtained from the pulp of human deciduous teeth are highly proliferative and plastic multipotent cells, which makes them a relevant model of stem cells, applied in several biomedical areas, with different purposes. Objective: Based on a brief review of the literature, the present work intends to present from conceptual aspects about stem cells, classifications, potential (in vitro and in vivo) applications in dental practice, cell culture, cryopreservation and its importance, ethical and regulatory aspects, as well as the role of the dental surgeon as the endorser responsible for the entire clinical stage that involves the process of collecting stem cells obtained from dental pulps for cryopreservation, with a view to using them under appropriate conditions, in accordance with scientifically proven and justified good laboratory and clinical practices.